The video lecture - Crook, Charles; Schofield, Louise (Elsevier, 2017)
Vocabulary for describing the structures, roles, and relationships characteristic of traditional, or ‘offline’, education has been seamlessly applied to the designs of ‘online’ education. One example is the lecture, delivered as a video recording. The purpose of this research is to consider the concept of ‘lecture’ as realised in both offline and online contexts. We explore how media differences entail different student experiences and how these differences relate to design decisions associated with each. We first identify five features of traditional lecturing that have been invoked to understand its impact. We then describe a taxonomy of online lecture design derived from digital artefacts published within web-based courses. Analysis of this taxonomy reveals six design features that configure differently the experience of lectures in the two presentational formats: classroom and video. Awareness of these differences is important for the practitioner who is now increasingly involved in developing network-based resources for learning.